A study of simultaneous patterning and alignment of semiconductor nanorods via polymerization-induced phase separation - Greener, Jesse (Langmuir : the ACS journal of surfaces and colloids, 2009)
We report simultaneous patterning and alignment of semiconductor nanorods (NRs) in nanorod-polymer films by using photolithographic polymerization-induced phase separation (PIPS). Exposure of the nanoparticle-monomer mixture to UV irradiation through a mask resulted in the site-specific photoinitiated polymerization of the monomer, which was followed with flow of the NRs from the areas rich in polymer to the areas rich in monomer. The orientation of NRs in the direction of flow was trapped in the polymerized films and characterized in polarization absorption experiments